Analysis of The EdLink Application Using The System Usability Scale (SUS) in Relation to User Satisfaction - Barut, Yuliandro Triatno Budianto; Manaf, Khaerul (Jurnal Media Digital, 2025)
This study aims to evaluate the usability and user satisfaction of the EdLink application using the System Usability Scale (SUS) method. SUS is a usability assessment tool consisting of 10 items—five positive and five negative—scored and converted into a total score from 0 to 100. The results are interpreted using the Grade Scale, Adjective Rating, Acceptability Ranges, and Net Promoter Score (NPS) to provide a comprehensive view of user perceptions. The EdLink application received a SUS score of 74.7, categorized as Grade B and rated “Good,” indicating that it is fairly easy to use and meets essential digital learning needs. It falls under the “Acceptable” range, although some limitations remain, such as the lack of automatic notifications, limited access to academic transcripts, and no academic data download feature. Most users were classified as “Passive” in the NPS, suggesting general satisfaction but limited enthusiasm to recommend the app